Uvod v integrirana vezja - Dogša, Tomaž (University of Maribor Press, 2022)
Introduction to Integrated Circuits. The purpose of this book is to describe the design techniques of simple analog and digital integrated circuits for undergraduate and graduate students. The assumed background of the reader is knowledge of basic semiconductor elements (e.g. diode, bipolar and MOS transistor) and basic discrete analog and digital building blocks. The knowledge of the simulation (SPICE) and manual DC and AC analysis is also needed. The emphasis is on CMOS circuits. Although NMOS circuits are today obsolete, they are included to better prepare readers for analysis of GaAs circuits, because it’s topology is quite similar to NMOS circuits. The book comprises seven chapters. It starts with the description of MOS transistor (characteristics, structure, CMOS technology, and layout design), and design methods, and ends with brief overview of modern microelectronics. At the end of certain chapters are exercises which solutions can be found in Tomaž Dogša: Osnove mikroelektronike [Elektronski vir]:zbirka vaj z rešitvami", 2019, ki je v DKUM.